2019
DOI: 10.12688/wellcomeopenres.15480.1
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion of ethical governance policy on sharing of biological materials and related data for biomedical research

Abstract: This paper considers how ethical norms on sharing of human biological materials and related data in international policy documents diffuse from global forums to national policies and practices. With focus on the domestic policies of four countries (i.e. Guinea, Argentina, India and Malawi), this paper seeks to explain policy diffusion by broadly applying an analytical framework wherein policy learning is one of four theories used to explain how countries learn policy norms from expert epistemic communities and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 5 publications
0
15
0
Order By: Relevance
“…At present, many LMIC countries have limited regulatory and governance structures for biobanking and data sharing 7 , and very few research institutions in these countries have formal data sharing policies. The case-studies and discussions at the GFBR meeting highlighted the importance of developing approaches to governing data sharing and biobanking which are appropriately tailored to context at national and institutional levels 8 . Such systems should ensure that the interests of study participants and communities, data providers and data users, and the public are appropriately recognized and respected 9 .…”
Section: Governancementioning
confidence: 99%
“…At present, many LMIC countries have limited regulatory and governance structures for biobanking and data sharing 7 , and very few research institutions in these countries have formal data sharing policies. The case-studies and discussions at the GFBR meeting highlighted the importance of developing approaches to governing data sharing and biobanking which are appropriately tailored to context at national and institutional levels 8 . Such systems should ensure that the interests of study participants and communities, data providers and data users, and the public are appropriately recognized and respected 9 .…”
Section: Governancementioning
confidence: 99%
“…Enabling participants to become partners in research 7. Community approval for research and publications in primary and secondary uses of samples and data the need to protect participants' rights in the governance of biobanking and genetic research 6,7,9,74,75 .…”
Section: Discussionmentioning
confidence: 99%
“…Eliciting public perceptions within India, on biomedical research using stored HBM samples and genome editing has found that there is a lack of confidence in regulatory processes among people, who believe mechanisms such as broad consent are instituted to primarily protect researchers interests 7,8 . Public engagement has the potential to build trust, accountability and fair research practices, however it is still at a nascent stage in India 8,9 .…”
Section: Introductionmentioning
confidence: 99%
“…That research was criticized by Rochmyaningsih ( 2018 ), who claimed that it benefitted international researchers at the expense of Indonesian scientists, with no benefit to the Bajau tribe. In Guinea, India and Argentina, HIC-based ethics policies tend to guide LIC-based health policies, such as for the Ebola virus (West Africa) and the Zika virus (Latin America) (Vaz, Palmero, and Nyangulu 2019 ). In Kenya, there is increasing awareness among RECs about the risks of ED via the abuse of local underdeveloped governance to exploit researchers in LICs (Chatfield et al 2021 ).…”
Section: Examples Of Ethics Dumpingmentioning
confidence: 99%